Identification of Leishmania species isolated from cutaneous leishmaniasis using molecular techniques in some provinces of Iraq - Manar Kareem; Sundus Nsaif Al Huchaimi; Rasha Fadhl Obaid; Huda A. Saleh (Journal of the Pakistan Medical Association, 2023)
Objectives: To detect Leishmania species in selected regions in Iraq. Method: The cross-sectional study was conducted from December 2021 to March 2022 at Al-Hashimyah General Hospital in Babylon province, and Al Diwaniya Education Hospital in AL-Qadisiah province of Iraq. The sample comprised patients with lesions suggestive of cutaneous leishmaniasis, as assessed by dermatologists. Direct smear was used for parasitological examination by lesion aspiration. Molecular technique was used for the characterisation of parasite genus and species. Positive direct smear specimens were analysed by nested-polymerase chain reaction using internal transcribed spacer-1 ribosomal ribonucleic acid gene. Results: Of the 120 specimens tested, 100(83.33%) tested positive; 59(59%) males and 41(41%) females. Most of the infections were leishmania major 92(92%), followed by leishmania tropica 8(8%). There were 80(80%) dry lesions and 20(20%) wet. Conclusions: Cutaneous leishmaniasis were mostly of tropica and major varieties in the studied areas. Keywords: Parasites, Dermatologists, Genes, rRNA, Cutaneous, Leishmania, Polymerase DNA.